2019
DOI: 10.1177/1054773818823333
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors and Triggers That May Result in Patient-Initiated Violence on Inpatient Psychiatric Units: An Integrative Review

Abstract: The aim of the present integrative review is to identify and describe risk factors and triggers that may result in patient-initiated violence on inpatient psychiatric units. Original studies were searched for in PubMed, PsycINFO, and the Cumulative Index to Nursing and Allied Health Literature. From the 826 identified publications, 18 were included for a synthesis. The results are presented in three themes, which demonstrate that patient characteristics, staff approach, and the ward environment are influencers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 77 publications
3
27
0
Order By: Relevance
“…Nurse managers' perception of team efficacy is on average four times more likely when the physical care environment is considered. Their perception of the importance of the physical environment echoes the results of a recent review which found the environment to be both a potential trigger and a factor for aggressive behaviours in psychiatric patients (Salzmann‐Erikson & Yifter, ). A calm, tidy and safe physical environment is known to play a role in reducing PVA (Bowers, ; National Association of State Mental Health Program Directors (NASMHPD) ; National Institute for Health & Care Excellence, ).…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Nurse managers' perception of team efficacy is on average four times more likely when the physical care environment is considered. Their perception of the importance of the physical environment echoes the results of a recent review which found the environment to be both a potential trigger and a factor for aggressive behaviours in psychiatric patients (Salzmann‐Erikson & Yifter, ). A calm, tidy and safe physical environment is known to play a role in reducing PVA (Bowers, ; National Association of State Mental Health Program Directors (NASMHPD) ; National Institute for Health & Care Excellence, ).…”
Section: Discussionmentioning
confidence: 70%
“…Their perception of the importance of the physical environment echoes the results of a recent review which found the environment to be both a potential trigger and a factor for aggressive behaviours in psychiatric patients (Salzmann-Erikson & Yifter, 2019 (Ulrich et al, 2008).…”
Section: Discussionmentioning
confidence: 74%
“…One such concept is Safewards, which focuses on primary prevention in nonthreatening situations. Conflict can arise from the patient's side, the medical personnel's side, or from the environment in the ward 11 . According to the creator of Safewards, Len Bowers, aggression is often correlated with medical personnel's interactions with patients 12 …”
Section: Introductionmentioning
confidence: 99%
“…Conflict can arise from the patient's side, the medical personnel's side, or from the environment in the ward. 11 According to the creator of Safewards, Len Bowers, aggression is often correlated with medical personnel's interactions with patients. 12 Initially, Safewards was used in acute psychiatric wards, but now its effectiveness is has been documented for other groups, also.…”
Section: Introductionmentioning
confidence: 99%
“…1 People with schizophrenia are closely related to the risk of increased violent behavior. 2 The incidence of violent behavior in Chinese psychiatric wards is 15.3%-53.2% among 3941 schizophrenic patients. 3 Studies from 10 countries in Europe illustrate the number of violent behavior of patients around 16-42% in some acute psychiatric and forensic services.…”
Section: Introductionmentioning
confidence: 99%